2017
DOI: 10.1016/j.otsr.2016.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Total hip arthroplasty using a cementless dual-mobility cup provides increased stability and favorable gait parameters at five years follow-up

Abstract: III, retrospective case-control series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…The survivorship for the dual-mobility cup used in this study agrees with previously reported midterm outcomes for this system [26,27]. In addition, our mean postoperative WOMAC and Merle D'Aubigne scores are comparable to those observed in mid-term follow-up series of cementless dual-mobility cups in primary THR [6,8,28].…”
Section: Discussionsupporting
confidence: 88%
“…The survivorship for the dual-mobility cup used in this study agrees with previously reported midterm outcomes for this system [26,27]. In addition, our mean postoperative WOMAC and Merle D'Aubigne scores are comparable to those observed in mid-term follow-up series of cementless dual-mobility cups in primary THR [6,8,28].…”
Section: Discussionsupporting
confidence: 88%
“…Fourth‐generation DM cups have proved effective at preventing IPD [11, 34, 46] and demonstrated promising complication and survival rates [18, 38, 39]. While originally intended for patients at risk of subluxation and dislocation, notably geriatric patients [1, 3] and those with femoral neck fractures [3, 24, 27, 28, 33, 41, 46] or neuromuscular deficit [9, 49], DM cups are increasingly used in younger and more active cohorts [31, 40, 49]. Their mid‐ to long‐term outcomes yet are scarcely documented and could reassure clinicians worldwide of their benefits and suitability for a wider range of indications [2, 25, 33].…”
Section: Introductionmentioning
confidence: 99%
“…A total of 521 records were identified using the search strategy, and 21 additional records were added by expert recommendation. After screening based on title and abstract, 197 articles were retrieved for full text review, and 63 articles met all inclusion criteria [ 2 , 10 , 29 90 ]. Full details of study attrition with exclusion reasons are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%